Formation of Single-Stranded DNA during DNA Transformation of Neisseria gonorrhoeae - Chaussee, Michael S. (American Society for Microbiology, 1998)
Neisseria gonorrhoeae is naturally competent for DNA transformation. In contrast to other natural prokaryotic DNA transformation systems, single-stranded donor DNA (ssDNA) has not previously been detected during transformation of N. gonorrhoeae. We have reassessed the physical nature of gonococcal transforming DNA by using a sensitive nondenaturing native blotting technique that detects ssDNA. Consistent with previous analyses, we found that the majority of donor DNA remained in the double-stranded form, and only plasmid DNAs that carried the genus-specific DNA uptake sequence were sequestered in a DNase I-resistant state. However, when the DNA was examined under native conditions, S1 nuclease-sensitive ssDNA was identified in all strains tested except for those bacteria that carried the dud-1 mutation. Surprisingly, ssDNA was also found during transformation of N. gonorrhoeae comA mutants, which suggested that ssDNA was initially formed within the periplasm.